MODEL LITERASI MEDIA UNTUK ANAK-ANAK SEKOLAH DASAR DENGAN MENGGUNAKAN MULTIMEDIA INTERAKTIF BERBASIS KEARIFAN LOKAL MASYARAKAT SALATIGA - Rini Darmastuti; Sri Winarso Martyas Edi; Erwien Christianto (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
The purpose of this research is find a model literacy a medium for elementary school students by the use of the interactive multimedia-based wisdom of local community in Salatiga. It uses qualitative method and ethnography communication approach. The data collection was done through observation and in-depth interviews with cultural and teachers primary schools in Salatiga. The results show that 1) The Local wisdom of Salatiga community has been applied in forms of appreciation, cooperation and tolerance based on the teachings of Raden Mas Said. 2) This local wisdom can be used as a basis for media literacy 3) There are two models of literacy media based on local knowledge, i.e., in the form of informal communication done by teachers and parents, and in the form of education through games. The game with Salatiga City setting and with figures of Wales and Asia as symbols of that tolerance is the local wisdom of Salatiga community which will be used as learning media in schools. This research contributes to provide media literacy model by using interactive multimedia based on local wisdom of the community in Salatiga.